ChemInform Abstract: A General Simple Methodology for Synthesis of Isonitriles Using Benzene‐1, 3‐disulfonyl Dichloride. Issue 31 (11th July 2013) - Ghorbani‐Vaghei, Ramin; Amiri, Mostafa; Veisi, Hojat
Abstract A facile protocol for the efficient transformation of formamides into isonitriles using 1, 3‐disulfonyl chloride as dehydration reagent is presented.